2021
DOI: 10.3390/agronomy11081563
|View full text |Cite
|
Sign up to set email alerts
|

Root System Morphology of Ipê-Roxo Tree Grown in Soil Subjected to Phosphorus Application in Subtropical Climate Region

Abstract: Phosphorus (P) availability in subtropical soils does not often meet the nutritional demand of native tree species such as the ipê-roxo tree (Handroanthus heptaphyllus); therefore, it is necessary to supply P at planting. However, the impact of P on root system growth remains unknown. The aim of the current study was to investigate the effect of P application on root morphology of H. heptaphyllus plants over a 36-month period in a subtropical climate region. During the experiment, the plants subjected to ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…They are also commonly used in reforestation programs and to restore degraded areas (Silva et al, 2021). The timber from this species is used in construction due to its high density, strength, and malleability (Parcianello et al, 2021). Due to important physiological properties resulting from the genus to which it belongs, which allow it to adapt to different environmental conditions and ecosystems, this species is often used to rehabilitate damaged areas (Berghetti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…They are also commonly used in reforestation programs and to restore degraded areas (Silva et al, 2021). The timber from this species is used in construction due to its high density, strength, and malleability (Parcianello et al, 2021). Due to important physiological properties resulting from the genus to which it belongs, which allow it to adapt to different environmental conditions and ecosystems, this species is often used to rehabilitate damaged areas (Berghetti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Two out of six manuscripts were from South America (Brazil and Chile) and deal with the effect of nutrient availability on root growth and plant development. Parcianello et al [1] investigated the effect of phosphorous (P) application on root morphology of Handroanthus heptaphyllus plants over a 36-month period in a subtropical climate region and demonstrated that the supply of P enhanced roots length and volume contributing to faster growth of plants. This research provides important information on the interaction between root growth and P availability showing the importance of optimal soil nutrient concentration for plant growth.…”
mentioning
confidence: 99%